Refinement of lamellar structures in Ti-Al alloy - Wei, Dai-Xiu; Koizumi, Yuichiro; Nagasako, Makoto; Chiba, Akihiko (Acta materialia, 2017)
The hot deformation behavior and refinement of Al-supersaturated α2-Ti3Al grains of Ti-40 at.% Al alloy were investigated by compression tests in a single α-hcp phase region at a strain rate of 1 s−1. Grains were significantly refined and homogenized by hot compression that produced more than a 50% reduction in the height of cylindrical samples. The grains were refined from 660 μm to 3.56 μm by 70% compression at 1473 K, and high densities of dislocations were introduced. In addition, the lamellar structures formed after subsequent aging of the compressed samples were significantly refined, owing to the refinement of Al-supersaturated α2-Ti3Al grains and the introduction of a high density of dislocations by hot compression. Moreover, the lamellar morphologies were affected by the distribution and density of dislocations in the α2-Ti3Al matrix. Ultra-fine lamellar structures with an average lamellar colony size of 4.1 μm and an average lamellar spacing of 25 nm were formed in the 70% compressed sample after aging at 1073 K for 10 ks In addition, a large number of ultra-fine γ grains were formed along the lamellar colony boundaries. [Display omitted]